The Religious Rights of Children Belonging to National Minorities and Indigenous Peoples - Zombory, Katarzyna (Religion and Children’s Rights, 2025)
Abstract:The enjoyment of the right to freedom of religion by children from cultural and religious minorities is vitally important for their harmonious development — as well as for preserving both their own cultural identity and that of their entire community. This chapter seeks to outline the international legal framework for protecting the religious rights of such children. The relevant legal standards can be found in general human rights instruments at both the universal and regional level, as well as in categorical human rights regimes — dedicated specifically to the protection of children and to the protection of national minorities and indigenous peoples. Some of the applicable provisions emphasise the child’s autonomous right to freedom of religion, while others support the child’s right to acquire and uphold the religious identity of his or her parents and the entire community. Keywords: children’s religious rights, religious identity, indigenous peoples, national minorities